The 2020 Pandemic in South Sudan: An Exploration of Teenage Mothers' and Pregnant Adolescent Girls' Resilience and Educational Continuity - Anne Corwith; Fatimah Ali (Journal on Education in Emergencies, 2022)
On March 13, 2020, the government of South Sudan implemented emergency lockdown measures in response to the COVID-19 pandemic. Fears that the pandemic would reverse efforts by the government and civil society to keep girls in school were realized and reported incidences of teen pregnancy increased. Prior to the pandemic, early marriage and teen pregnancy in South Sudan were already of extreme concern, as the country reported the seventh-highest child marriage rate in the world. Countrywide data from 2019 indicated that only 34 percent of the students who sat for primary exams were girls. We conducted this qualitative study to explore the resilience factors that adolescent mothers and pregnant adolescents relied on during the COVID-19 lockdowns in Maiwut Town, South Sudan, to enable them to return to school and continue their education. Our research revealed that, despite struggling to meet their basic needs, receiving weak support from their social networks, and experiencing violence and persistent negative gender roles, these adolescent mothers and pregnant adolescents exhibited resilience in their aspirations to return to school and become financially independent. By centering this research on the voices of this vulnerable population, we are able to recommend what we argue are more effective and targeted interventions for organizations that are working in this and similar emergency contexts.